Improving the care of veterans: The role of nurse practitioners in team‐based population health management. Issue 11 (31st August 2017) - Hobson, Alexandra; Curtis, Alexa
Abstract: Background and purpose: Improving healthcare delivery for U.S. veterans is a national priority. The Veterans Health Administration (VHA) employs a variety of team‐based, population health strategies to address critical issues in veterans' health including the effective management of chronic disease. Nurse practitioners (NPs) are integral members of the VHA patient care team with a substantial role to play in the organization and delivery of healthcare services for veterans. This report explores the contributions of NPs in team‐based, population health strategies within the VHA. Methods: This review of the literature examines peer‐reviewed articles published between 2006 and 2017 to explore the contributions of NPs in team‐based, population health strategies within the VHA. Search words include veterans, VHA, NPs, population health, panel management, and chronic disease . Conclusions: NPs are vital members of the VHA primary care team; however, there is a dearth of available evidence reflecting the unique contribution of NPs within VHA team‐based, population health management strategies. Implications for practice: The VHA adoption of full practice authority for NP practice provides NPs with an expanded capacity to lead improvements in veterans' health. Future research is needed to fully understand the unique role of the NP in the delivery of population health management strategies for veterans.